Change in storage symptoms after transurethral resection of prostate: a prospective observational study - Luitel, BR; Gupta, DK; Chalise, PR; Subedi, P; Chapagain, S; Sharma, UK; Gyawali, PR; Shrestha, GK; Joshi, BR (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Patients with enlarged prostate generally rate their storage symptoms (frequency, urgency and nocturia) as the most bothersome as these symptoms interfere more with daily activities and have huge impact on quality of life. Effect of transurethral resection of prostate (TURP) on storage symptoms is unknown. Objective of the study is to assess the change in storage symptoms in patients undergoing TURP. Methods: A prospective observational study was conducted at the author’s institute from August 2011 to July 2012. Patients undergoing TURP for moderate to severe lower urinary tract symptoms (LUTS) secondary to benign enlargement of prostate were included. Patients were evaluated by International prostate symptom score (IPSS) questionnaires. The question number 2, 4 and 7 of the IPSS questionnaire gave the storage symptom subscore (0-15). After initial evaluations, the patients underwent TURP. After 3 months, the IPSS was reevaluated and the change in storage symptom was analyzed. Results: A total of 57 patients who had undergone TURP were eligible for final data analysis. Majority of the patients had severe bothersome LUTS with mean IPSS score of 24.6±6. The baseline storage symptom subscore was 11.1±3. After 3 months of follow-up, there was significant decrease in total IPSS score and both of its subscores. On comparing the mean change in storage and voiding subscore, there was less decrement in storage subscore which was statistically significant (p=0.001). Conclusions: This study showed that after TURP change in voiding subscore occurs more than storage subscore and storage symptoms may not revert to normal.